Educational planning strategic, tactical, and operational - Kaufman, Roger A.; Watters, Kathi; Herman, Jerry (Scarecrow Press, 2002)
"Expert presentation of holistic planning for a learner-focused educational system. Integrates curriculum, facilities, personnel, finance, educational technology, and other significant planning tactics."